Model Deteksi Dini Gangguan Psikologis Pegawai Berdasarkan Srq-29: Pendekatan Demografis dan Unit Kerja pada Perusahaan Pupuk dan Kimia di Jawa Timur - Irwan Prasetyo; Indriati Paskarini (Jurnal Sosial Humaniora, 2025)
Employee mental health plays a crucial role in sustaining organizational productivity, particularly in high-risk industries such as fertilizer and chemical manufacturing. This study aims to identify early psychological distress among employees in fertilizer and chemical companies in Gresik City using the Self-Reporting Questionnaire (SRQ-29), with particular attention to demographic characteristics and work units. Quantitative research design was employed, using primary data collected through questionnaire distribution. Data analysis included validity and reliability testing, multiple linear regression, coefficient of determination (R²), and simultaneous (F) testing. The SRQ-29 instrument was found to be valid (r = 0.496; p = 0.000) and reliable (Cronbach’s Alpha = 0.738). Regression analysis indicated that age and gender significantly influenced SRQ-29 scores, while work unit showed no significant effect. Although all variables collectively affected psychological distress, the explanatory power of the model was very limited (R² = 0.020). These findings suggest that demographic factors contribute only marginally to employee mental health, highlighting the greater importance of other factors such as workload, work-related stress, social support, and physical working conditions. The study underscores the need for early detection mechanisms and comprehensive mental health policies in high-risk industrial settings.